2012
DOI: 10.1186/1743-8977-9-2
|View full text |Cite
|
Sign up to set email alerts
|

A mixture of anatase and rutile TiO2 nanoparticles induces histamine secretion in mast cells

Abstract: BackgroundHistamine released from mast cells, through complex interactions involving the binding of IgE to FcεRI receptors and the subsequent intracellular Ca2+ signaling, can mediate many allergic/inflammatory responses. The possibility of titanium dioxide nanoparticles (TiO2 NPs), a nanomaterial pervasively used in nanotechnology and pharmaceutical industries, to directly induce histamine secretion without prior allergen sensitization has remained uncertain.ResultsTiO2 NP exposure increased both histamine se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 57 publications
0
46
1
1
Order By: Relevance
“…function by activating signaling pathways that involve activation of different isoforms of phospholipase C (PLC) and generation of IP 3 that eventually leads to an increase in [Ca 2+ ] i [66]. Previous work has demonstrated that various ENMs can induce a sustained increase in [Ca 2+ ] i in different cell models including mast cells [6769]. Our current studies show that exposing mast cells to AgNPs resulted in a rapid increase in [Ca 2+ ] i .…”
Section: Discussionmentioning
confidence: 99%
“…function by activating signaling pathways that involve activation of different isoforms of phospholipase C (PLC) and generation of IP 3 that eventually leads to an increase in [Ca 2+ ] i [66]. Previous work has demonstrated that various ENMs can induce a sustained increase in [Ca 2+ ] i in different cell models including mast cells [6769]. Our current studies show that exposing mast cells to AgNPs resulted in a rapid increase in [Ca 2+ ] i .…”
Section: Discussionmentioning
confidence: 99%
“…In rats some NP can interact and stimulate mast cells to secrete histamine, thereby modifying allergic responses in atopic models. 116 Inhalation of gold or TiO 2 NP enhanced lung inflammation and airway hyper-reactivity (AHR) in a mouse model of isocyanate-induced asthma. 117 These effects may be due to direct activation of lung DC subset by inhaled NP.…”
Section: Biological Effectsmentioning
confidence: 99%
“…The cellular localization of nanomaterials may be particularly important in determining their toxicity. For instance, iron oxide NPs may exert catalase-like activities at cellular pH but in acidic environments like lysosomes they have peroxidase-like activity, resulting in the catalysis of H 2 O 2 into hydroxyl radicals (Chen et al, 2012a). Furthermore, lysosomes present acidic pH conditions which could favor nanomaterial dissolution and even low-solubility NPs such as SiO 2 have been shown to dissolve over time within cells (Quignard et al, 2012).…”
Section: 3 Other Cellular Mechanisms Induced By Nanomaterialsmentioning
confidence: 99%